2018
DOI: 10.4314/jfas.v9i6s.67
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Zakat in the capital structure theory

Abstract: Islamic financial instruments are subject to taxes and zakat holders. Therefore, it is important to investigate the implementation of corporate taxes and corporate zakat in capital structure compositions. In order to model corporate zakat in terms of conventional capital structure th those theories in depth. The introduction of zakat are based on the conventional static trade-off theory developed by previous research

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Consequently, the financial distress faced by these institutions can be mitigated. This aligns with previous research that has identified Zakat as a potential variable with advantageous implications for the financial performance of both states and companies (Noor et al, 2015;Javaid & Al-Malkawi, 2018;Sanusi et al, 2018;Rizki et al, 2019). In light of these considerations, this research proposes the following hypothesis: H1 : Zakat has negative significant relation to financial distress Table 1 below presents the descriptive statistical data for the following indicators and variables used in this study.…”
Section: Zakat and It's Indirect Benefits For Islamic Banking Institu...supporting
confidence: 77%
“…Consequently, the financial distress faced by these institutions can be mitigated. This aligns with previous research that has identified Zakat as a potential variable with advantageous implications for the financial performance of both states and companies (Noor et al, 2015;Javaid & Al-Malkawi, 2018;Sanusi et al, 2018;Rizki et al, 2019). In light of these considerations, this research proposes the following hypothesis: H1 : Zakat has negative significant relation to financial distress Table 1 below presents the descriptive statistical data for the following indicators and variables used in this study.…”
Section: Zakat and It's Indirect Benefits For Islamic Banking Institu...supporting
confidence: 77%